Transforming Conservation : A Practical Guide to Evidence and Decision Making - William J. Sutherland (Open Book Publishers, 2022)
There are severe problems with the decision-making processes currently widely used, leading to ineffective use of evidence, faulty decisions, wasting of resources and the erosion of public and political support. In this book an international team of experts provide solutions. The transformation suggested includes rethinking how evidence is assessed, combined, communicated and used in decision-making; using effective methods when asking experts to make judgements (i.e. avoiding just asking an expert or a group of experts!); using a structured process for making decisions that incorporate the evidence and having effective processes for learning from actions. In each case, the specific problem with decision making is described with a range of practical solutions. Adopting this approach to decision-making requires societal change so detailed suggestions are made for transforming organisations, governments, businesses, funders and philanthropists. The practical suggestions include twelve downloadable checklists. The vision of the authors is to transform conservation so it is more effective, more cost-efficient, learns from practice and is more attractive to funders. However, the lessons of this important book go well beyond conservation to decision-makers in any field.